Split diesel injection effect on knocking of natural gas/diesel dual-fuel engine at high load conditions. (1st December 2020) - Yousefi, Amin; Guo, Hongsheng; Birouk, Madjid
Highlights: Advancing SODI increases knocking intensity of NDDF engine at high load conditions. Split injection reduces knocking intensity of NDDF engine at high load conditions. Split injection decelerates flame kernels' growth and dilutes the unburned end-gas. NDDF engine with split injection can reach a maximum ITE of 39.4%. Abstract: Advancing the start of diesel injection timing is an effective way to enhance thermal efficiency and reduce greenhouse gas (GHG) emissions of natural gas/diesel dual-fuel (NDDF) engine. However, severe thermodynamic conditions under high engine load conditions may increase the propensity for engine knocking when advancing the start of diesel injection (SODI). In this study, the strategy of split diesel injection (two-pulse injection) is used and its feasibility as a method to reduce knocking intensity and improve thermal efficiency of NDDF engine is investigated. The results reveal that advancing single diesel injection timing significantly increases knocking intensity, whereas split diesel injection strategy decreases knocking intensity. The results also show that, when using split diesel injection, the flame kernels do not propagate as fast and deep as in the case of single diesel injection. This slows down the pressure and temperature rise rate in the unburned end-gas region and thus reduces knocking tendency. Moreover, the early partially burning of the premixed natural gas – air mixture in the squish region dilutes the unburned end-gas and consequently makes it resistant to auto-ignition. NDDF engine with split diesel injection can reach a maximum thermal efficiency that is comparable to that observed under knocking conditions of single diesel injection. Using either, single or split, diesel injection strategy reduces GHG emissions of NDDF engine (up to 12%) compared to its counterpart diesel engine. However, the lowest GHG emissions of NDDF engine with single diesel injection strategy is recorded under knocking conditions.